Influence of High-Intensity Zr Ion-Beam Treatment on Deformation and Fracture of 12Cr1MoV Steel under Static, Cyclic and Dynamic Loadings; Key Engineering Materials; Vol. 712 : Advanced Materials for Technical and Medical Purpose (AMTMP 2016) - Vlasov I. V. Ilya Viktorovich; Panin S. V. Sergey Viktorovich; Sergeev V. P. Viktor Petrovich; Naidfeld V. Vasilii; Maruschak P. Pavlo; Ovechkin B. B. Boris Borisovich (Electrophysical and Electrochemical Methods and Technologies of Materials Treatment, 2016)
Title screen